Konsep Tauhid Ibnu Taimiyah dan Pengaruhnya Terhadap Pembaharuan Pemikiran Islam - Qois Azizah bin Has (Aqlania, 2021)
Discussions about tawhid have been controversial and debated by previous scholars. That is because some of them express God's Oneness using logic. However, Ibn Taymiyah tried to reform the nationalized tawhid based on the Qur'an and the Sunnah. And unequivocally criticize arguments that are not all with Islamic values. However, the renewal of Ibn Taymiyah's thinking was not immediately accepted by some scholars. Shaikh Taqiyuddin as-Subki, for example, judged ibn Taymiyah's reform discourse to be rigid and out of al-ittiba' and switched to al-ibtida'. Thus this discourse of renewal is an oddity carried out by Ibn Taymiyah. However, although it is considered strange, Ibn Taymiyah's thinking is considered more likely to be exclusive. So the study of religion makes Islam easy to understand by Modern Muslims. Including the concept of tawhid by classifying it into three parts. None other than that modern Muslims can understand tawhid universally and comprehensively. By studying some of Ibn Taymiyah's books and other supporters the author tried to explain the concept of tawhid and the discourse of renewal.